(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: Thymus is intimately related to the immuno regulatory mechanism of the body, its weight in general as well as at different age in a particular population might also be related to the overall immune status of that population. Thus the knowledge of the weight of the thymus at different ages may be helpful in planning of the medical and surgical treatment of thymus related problem as well as dealing patients from immunologic aspects Objective: To measure the age related changes in weight of the thymus gland of Bangladeshi people Study design: A descriptive type of study Place and period of study: The study was carried out in the Department of Anatomy, IPGMR Dhaka from October 1996 to March 1997. Materials: 40 (forty) thymuses from Bangladeshi cadaver of either sex were taken for this study. Method: The collected samples were divided into four age groups ranged from still born to sixty years old individuals and comparative studies were done between different age groups. Result: The thymuses increased significantly in weight steadily through the increasing age groups from the still born babies to <16yrs and then declines through the age still higher. Conclusion: In the present study the weight of the thymus increases through the increasing age groups and then declined. Key words: Thymus; Weight DOI: 10.3329/bja.v8i1.6101 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 10-12